Perancangan Enkripsi Pada Citra Bitmap Dengan Algoritma Des, Triple Des, dan Idea - Yosanny, Agustinna (Bina Nusantara University, 2010)
Rapid development of Information Technology causes information can access easier without space boundaries. Image is a form of information, which contains many information. Some image contains confidential information that cannot distribute to unauthorized persons. Therefore, image encryption application is create to encrypt part of image that has confidential information. The image encryption application is encrypt image by applying DES, Triple DES, and IDEA algorithms. The research was applying analysis and design methodology. The analysis methodology was undertaken through literature study and algorithm research and testing. The design methodology was undertaken through database, features, system, and screen layout design. Results of the research are image encryption application that can encrypt part of image and or all of image by applying three algorithms such as DES, Triple DES, and IDEA. This application is show comparation of these algorithms. In conclusion, method of encryption can apply to image, so that confidential information of the image can protect from unauthorized person.